PARENTS INVOLVEMENT IN CHILDREN SCHOOL LIFE - Bahouty, Saker (My University, 2016)
Parents' involvement in the life of their children in general and in the education system in particular is an accelerating process in recent years both in the world and in Israel. The concepts "participation", "intervention" and "involvement" are central concepts serving as tools for description of the character and quality of relations between the parents and the school.